Three approaches to school-university partnerships among teacher residencies: can HBCUs lead the way to an equity-centric model? - Valerie Hill-Jackson (Emerald Publishing, 2024)
Purpose - School-university partnerships (SUPs) probe a range of P12 challenges and interests, with teacher residencies being chief among them. Because historically black colleges and universities (HBCUs) have impressive track records (Hill-Jackson, 2017) and knowhow (Marchitello & Trinidad, 2019; Petchauer & Mawhinney, 2017) in preparing teacher candidates to work effectively in diverse schools, this paper seeks deeper understandings of the types of SUPs for teacher residency collaborations employed by traditional versus HBCU programs. Design/methodology/approach - This article draws upon the self-study as a methodology to review a SUP for a teacher residency at an HBCU in the southwestern United States to illustrate an equity-centric model. Findings - Leveraging an equity and third space perspective, three separate approaches to the SUPs are unpacked to establish the outline for this proposal: ceremonial, conventional and communal teacher residency approaches. Originality/value - A novel typology of three distinct approaches to SUPs for teacher residencies is outlined to establish the extent to which equity is foregrounded among teacher residencies.